Combining Servqual and Kano: Justification for Best Action and Its Selection Process - Supangkat, Hendrarto Kurniawan; Savitri, Gusti Ayu Made Hanny Dian (Jurnal Kawistara, 2024)
This study aims to enhance the existing literature on the integration of Servqual and Kano concepts by providing a comprehensive justification for recommending improvement actions to service attributes. By utilizing a theoretical service model that considers factors previously overlooked, such as the impact on revenue and cost, performance variability, diminishing marginal utility in consumption, and diminishing marginal product of resources, this study offers propositions and proofs for the best actions in each paired category of service attributes within the combined Servqual and Kano assessments. The findings are presented in the form of an evaluation table, which links each paired category of attribute with its respective optimal action. Importantly, this study introduces novel perspectives on the definition of the best action and the basis for its selection. Unlike previous works that solely focus on customer satisfaction, this research defines the best action from the perspective of the service provider whose primary goal is to maximize profit. The proposed procedure for determining the best action obtained in this study is more justifiable, as it relies less on the ambiguous process of correctly identifying the final categories of attributes in both models. To illustrate the new integration process, an example based on simulated data is also provided. Overall, this study contributes to the field by offering a comprehensive and justified approach to improving service attributes through the integration of Servqual and Kano concepts.